The epidemiology of AmpC‐producingEscherichia coliisolated from dairy cattle faeces on pasture‐fed farms. Issue 10 (October 2021) - Burgess, Sara A.; Cookson, Adrian L.; Brousse, Lisa; Ortolani, Enrico; Benschop, Jackie; Akhter, Rukhshana; Brightwell, Gale; McDougall, Scott
Abstract : Introduction. : Antibiotic use, particularly amoxicillin‐clavulanic acid in dairy farming, has been associated with an increased incidence of AmpC‐hyperproducing Escherichia coli . Gap statement. : There is limited information on the incidence of AmpC‐hyperproducing E. coli from seasonal pasture‐fed dairy farms. Aim. : We undertook a New Zealand wide cross‐sectional study to determine the prevalence of AmpC‐producing E. coli carried by dairy cattle. Methodology. : Paddock faeces were sampled from twenty‐six dairy farms and were processed for the selective growth of both extended‐spectrum beta‐lactamase (ESBL)‐ and AmpC‐producing E. coli . Whole genome sequence analysis was carried out on 35 AmpC‐producing E. coli . Results. : No ESBL‐ or plasmid mediated AmpC‐producing E. coli were detected, but seven farms were positive for chromosomal mediated AmpC‐hyperproducing E. coli . These seven farms were associated with a higher usage of injectable amoxicillin antibiotics. Whole genome sequence analysis of the AmpC‐producing E. coli demonstrated that the same strain (<3 SNPs difference) of E. coli ST5729 was shared between cows on a single farm. Similarly, the same strain (≤15 SNPs difference) of E. coli ST8977 was shared across two farms (separated by approximately 425 km). Conclusion. : These results infer that both cow‐to‐cow and farm‐to‐farm transmission of AmpC‐producing E. coli has occurred.